Software for the basketball player's evaluation in real time - Ibanez, S. J.; Perez, M. A.; Macias, M. (International Journal of Performance Analysis in Sport, 2003)
During training and competition, head coaches must take technical and tactical decisions, basing them on his intuition and experience without the support of objective data. For this reason, it is important to develop indicators for the registration, analysis and evaluation of quantitative and qualitative elements in the practice of sports. The computer application that we present here is an attempt to advance in the development of these instruments, allowing for the compilation, analysis and evaluation of the players' actions in real time. Our aim is to try to help head coaches to take inter-active decisions, by providing them with information on variables that traditionally have depended on mere subjectivity (technical and tactical actions that conventional statistics do not collect, sequence and effectiveness of the game systems, etc), making possible the quantification and analysis in real time. In order to develop the program, we have objectively established several indicators which allow the information demanded by head coaches during the training or competition to be collected in real time. Once the indicators were validated we proceeded to design and create the instruments (hardware and software) for compiling the information, analyzing it and passing it on to the head coach during the training session or competition. The recording of players' actions during the development of a basketball game, for example, entails several problems, mainly due to the speed at which the various actions to be recorded occur. In order to solve this, several different people must be involved in the collection of information, each one of them specialized in a different phase of the game, for example one in offence and one in defence, each of them assigned to one team, and all of them must co-operate to collect all the information without any being lost. The entry of a larger number of variables to analyse, both quantitatively and qualitatively, together with their quantification, enables us assess the players in a more accurate way which is more attuned to reality. With this program, it is also possible to view the game events in a different way: according to a player, a team, actions and in real time. All the data obtained will be stored for a later analysis. Future works are aimed at the improvement of devices related to teams. In particular, improvements will be aimed at making the program easier to transport and operate for use inside sport centres by removing the need for cable connection of the equipment. Likewise, the data entry devices are one of the applications which we could be optimized and which we will keep on working on.